The Effect of Price, Competitor Attractiveness, and Consumer Involvement on Brand Switching Behavior from Samsung Smartphone in Malang City - Marsellina Hedy Fatdiana Cen (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
Technologycaly development can be marked with the emergence of smartphones of various brands. The numerous brands of smartphone can create a tendency of brand switching on consumers. Brand switching behavior caused by price, attractiveness of competitor, and consumer involvement. This research aims to determine the effects of Price, Competitor Attractiveness, and Consumer Involvement on Brand Switching for Samsung smartphone in Malang city.This research is explanatory research with quantitative and survey method. This study used 120 samples of Samsung smartphone consumers that have switched to another smartphone brand in Malang. Those samples were taken by using a purposive sampling technique. Test instruments that are used for testing the research instruments are validity test, reliability test, and classical assumption test. The analysis methods that were used are multiple linear regression and hypothesis testing.The result of hypothesis testing concludes that Competitors Attractiveness has significant effect toward Brand Switching while Price and Consumer Involvement do not have significant effect on Brand Switching.Key words : Price, Competitor Attractiveness, Consumer Involvement, Brand Switching